The Urgency of Exclusive Rights Protection for Trademark Licensees in Indonesia - Noorvicky, Rizky; Purwadi, Hari; Latifah, Emmy (JURNAL AKTA, 2024)
A trademark is essentially an exclusive right granted by Indonesian law to the licensee. But the facts are practically different from the circumstances where provisions made by bureaucracy no longer have authority as trademark licensees granted by trademark owners. With regard to the case under discussion, such important declaration of exclusive rights in the Letter of Authorization or authorization granted by the trademark owner whose registrar is through the Madrid Protocol to the licensee of trademark in Indonesia that is not recorded exclusively. This study aims to examine and analyze how the legal protection of the proprietor of the exclusive rights of the trademark under a licensing agreement and what the meaning of “exclusive rights” for the licensee of a trademark relates to the existence of a case of trademark infringement that is supposed to violate the provisions of Law No. 20 of 2016 on Trademarks and Geographical Indications. The research method used is normative jurisprudence. The findings of this study are that the weakness of the substance of legislation and the bureaucracy of law enforcement is unprofessional.